Investigation of Anti-inflammatory, Antipyretic and Analgesic Activities of Citrullus colocynthis in Albino Rats through in vivo and Pharmacoinformatics Studies - Hassan, Mubashir; Zahra, Nureen; Shafi, Amtul; Shahzadi, Saba; Moustafa, Ahmed; Kloczkowski, Andrzej (Recent Advances in Anti-Infective Drug Discovery, 2024)
Introduction: Hyperpyrexia, algesia and inflammation are pathological disorders which are treated with synthetic as well as herbal medications. Aims: The basic aim of the present study is to evaluate the ethnopharmacological activities of phytoconstituents that are present in C. colocynthis (fruit extract) by using in vivo and in silico studies. Methods: Thirty-six albino rats were used in our studies with an average weight between 150-170 g. Anti-inflammatory activity was investigated using carrageenan (an extract from a red seaweed) that induced edema in albino rat paws. However, in antipyretic and analgesic activity studies, yeast and acetic acid were used to cause pyrexia or algesia, respectively. Different doses of acetone fruit extract were used to treat inflammation, pyrexia and algesia. Results: Our results showed that the maximum percentage inhibition of acetonic fruit extract in anti-inflammatory and analgesic activities was observed at 70% and 100%, respectively, with 400 mg/kg doses, and in pyretic activity the maximum inhibitory percentage was 86% with a 100 mg/kg dose. In in silico analysis, we have shown that bioactive compounds (α-spinasterol, ascorbic acid and chlorogenic acid) found in fruit extract have outstanding inhibition properties that involves proteins PTGS2, TLR2 and TRPV4. C. colocynthis fruit extract shows results that are statistically significant (p < 0.005) and comparable to a reference drug. Acetonic fruit extract of C. colocynthis can be used as a natural and safe remedy with no side effects. Conclusion: Both in vivo and in silico studies on chlorogenic acid, ascorbic acid and α-spinasterol have shown that these are inhibitory compounds that can be used for boosting the immune response.
Keywords: α-spinasterol